ANALISIS PENGARUH PENINGKATAN FREKUENSI PENERBANGAN DAN FASILITAS PARKIR TERHADAP KEPUASAN PELANGGAN DI PARKIR BANDARA HALIM PERDANAKUSUMA JAKARTA TIMUR - Yosepha, Sri Yanti; Zai, Tri Juniman (Feb Universitas Dirgantara Marsekal Suryadarma, 2017)
This study aimed to examine the effect of the analysis the increase in flight and parking facilities to the level of customer satisfaction at the parking Halim Perdanakusuma Airport empirically, either partially and simultaneously.